A relict sulfate–methane transition zone in the mid-Devonian Marcellus Shale. (1st June 2016) - Niu, Danielle; Renock, Devon; Whitehouse, Martin; Leone, James; Rowe, Harry; Landis, Joshua; Hamren, Keith; Symcox, Carl W.; Sharma, Mukul
Abstract: A barium-enriched interval of Marcellus Shale (Middle Devonian Oatka Creek Formation) from a core in Chenango County, NY contains ∼100 μm diameter ellipsoidal grains with variable mineralogical compositions between pure barite and pure pyrite endmembers. Petrographic characterization and in-situ sulfur isotope analysis by Secondary Ion Mass Spectrometry (SIMS) was performed to better understand the diagenetic conditions under which these grains form and are preserved in the shale. Textural relationships suggest partial to complete pseudomorphic replacement of ellipsoidal barite by pyrite. Spatially, the ellipsoidal grains are concentrated in discrete layers parallel to original bedding and intervals within these layers often contain grains with similar degrees of replacement. The fraction of barite replaced by pyrite between these intervals can vary significantly, which is remarkable considering these intervals are separated by stratigraphic distances on the order of mm to cm in the shale (depths equivalent to deposition over 10's–1000's of years). The mean δ 34 S of barite and pyrite in ellipsoidal grains is 63.3 ± 3.6‰ and 2.2 ± 3.0‰, respectively, indicating that the grains are authigenic. Mass balance calculations based on density and stoichiometric differences between barite and pyrite indicate that reduction of sulfate from barite alone cannot be the sole source of sulfur in the replaced grains: only ∼23% of sulfur in pyrite comes from the dissolution of barite while the remainder derives from an additional source with δ 34 S = −17.6 ± 1.3‰. We suggest that pseudomorphic replacement of barite led first to the formation of greigite (Fe3 S4 ), where one mole of sulfur was provided by barite and the other three moles of sulfur were contributed by FeS(aq) ; the latter formed by reaction of Fe 2 + with sulfide from microbial sulfate reduction. Transformation of greigite to pyrite occurred via the sulfur addition and/or iron loss pathways. These observations suggest the following mechanism for the replacement of barite by pyrite in the ellipsoidal barite grains: (1) burial of authigenic barite below the sulfate–methane transition zone (SMTZ), and (2) partial to complete dissolution of the grain and concomitant precipitation of greigite (and its subsequent transformation to pyrite) in the presence of pore water depleted in sulfate and enriched in FeS(aq) and polysulfides. We suggest that closely-spaced intervals containing different barite to pyrite ratios may reflect fine-scale temporal shifts or fluctuations in the position of the SMTZ due to variable rates of methanogenesis and/or sedimentation during diagenesis.